Green Marketing or Greenwashing: How Consumers Evaluate Environmental Ads - Pham, Nguyen T.; Barretta, Paul G. (Journal of Applied Business and Economics, 2024)
Over the past few years, there has been a significant increase in the number of cases related to greenwashing. This research investigates how consumers develop green skepticism to react to greenwashing practices. In two studies, we demonstrate that environmental ads (either vague or specific ads) are more effective in persuading weak-attitude consumers resulting in lower green skepticism than strong-attitude consumers. In contrast, strong-attitude consumers exhibit a backfiring behavior when presented with vague ads, evidenced by their higher level of green skepticism and lower WTP for products featured in the ads. More interestingly, specific ads are effective among strong-attitude consumers, lowering their green skepticism and increasing their WTP. Our research has theoretical and managerial implications for green marketing communication.